Ombudsman : an alternative organization to redress of people’s injustice - CHEINPRADIT, KREINGKRAI (Journal of Thai Ombudsman, 2025)
This article aims to study and present the mechanisms, duties and powers of the Ombudsman, with the hope that the readers of the article will understand the specific duties and powers of the Ombudsman more, so that they can use the Ombudsman’s services to solve problems and protect their rights and freedoms more effectively. At present, there are several governmental units that function to receive complaints and investigate to redress the problems that happened to people. There are the government agencies, the central units, and constitutional independent organization, where each intends to help alleviating problems and suffering that resulted from the operation by the governmental units and government officers by relying on the mechanism of action following duties and powers provided by the law. The Ombudsman is an independent organization under the Constitution, a channel provided by the Constitution for the people to solve problems of suffering or injustice received from actions by the government. It has a unique power mechanism that cannot be found in other channels or methods of the government. It can also be used to solve specific problems of each case while protecting public interests. At the end of this article, suggestions are presented to help increase the efficiency of the existing power mechanism of the Ombudsman so that it can be operated more effectively.